FORMING OF CREATIVE THOUGHT OF STUDENTS AS BASIS OF INNOVATIVE DEVELOPMENT OF SOCIETY - Мойсеєнко, Л. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article the actuality of activity drive of creative’s potential of future specialists have been analyzed. There have been also validly investigated results of implementation of creative training of students for improvement of subject’s sensitivity, development synergy and activation of serendipity components of creative process as an example of creative mathematical thinking.